Development strategy for halal tourism village in Gedepangrango, Sukabumi district - Nasyafira, Hanifah Zahra; Wiliasih, Ranti; Nursyamsiah, Tita (Halal Studies and Society, 2024)
Halal tourism is recognized as a significant contributor to the economy and has promising potential. The number of tourism village with halal concepts in Indonesia is limited, but Gedepangrango Village in Sukabumi District has great prospects for development. Therefore, this study aimed to use the Analytical Network Process (ANP) as well as Strengths, Weaknesses, Opportunities, and Threats (SWOT) methods to analyze strategy for developing halal tourism village in Gedepangrango. The results showed that SWOT significantly impacted development of halal tourism village. The analysis confirmed tourism potential in agriculture, nature, and culture within village, but governance has not been optimal. Furthermore, development plans were consistent with the Regional Medium-Term Development Plan of Sukabumi District, and there was competition from other tourism village. Based on the results, the primary focus should be raising the capacity of human resources to develop halal tourism village.